Characteristics of Simalambuo (Lophopetalum sp.) wood from Nias Island, North Sumatra Province, Indonesia - APRI HERI ISWANTO; DWIVIA WAHYU AMANDA; SAHARMAN GEA; ARIDA SUSILOWATI; WIDYA FATRIASARI; ATMAWI DARWIS; M. ADLY RAHANDI LUBIS; TITO SUCIPTO; SYAHIDAH SYAHIDAH; NIKEN SUBEKTI; RUDI HARTONO; JAJANG SUTIAWAN; WAHYU HIDAYAT; NAM HUN KIM (Society for Indonesian Biodiversity, 2023)
Abstract. Iswanto AH, Amanda DW, Gea S, Susilowati A, Fatriasari W, Darwis A, Lubis MAR, Sucipto T, Syahidah, Subekti N, Hartono R, Sutiawan J, Hidayat W, Kim NH. 2023. Characteristics of Simalambuo (Lophopetalum sp.) wood from Nias Island, North Sumatra Province, Indonesia. Biodiversitas 24: 4193-4201. Simalambuo (Lophopetalum sp.) wood is commonly used for construction materials in Nias Island, North Sumatra Province especially in the aftermath of the devastating earthquake that affected the region. However, information regarding the fundamental characteristics of this wood has not been available. Therefore, this research aimed to evaluate the basic properties of Simalambuo wood, such as its physical, mechanical, chemical, and natural durability. The destructive method was used to determine the physical and mechanical parameters (i.e., specific gravity, moisture content, shrinkage, MOE, MOR, and hardness) using a small clear specimen sample under the BS 373 standard (1957). The chemical components of wood (i.e., holocellulose, cellulose, lignin, extractives) were analyzed using a variety of methods, including CRC Press methods, LAP NREL 003 standard, and TAPPI. Meanwhile, the SNI 7207-2014 standard was utilized to evaluate its resistance against subterranean termites. The results showed that Simalambuo wood has an average specific gravity of 0.42 and a T/R ratio of 1.78. Based on its specific gravity, the wood is classified within the strength class III-IV. It also exhibits a reduced cellulose and extractive content, along with a higher proportion of lignin. In terms of durability, it is classified as class IV, implying non-resistance to termites’ attack and necessitating wood preservation treatment for its practical application. The findings of this study suggest the application of this wood is recommended for light construction, furniture, and other functions, but not for heavy construction.